Cranial ultrasound findings in asphyxiated term neonates and their correlation clinically with hypoxic ischemic encephalopathy staging - Ganesan, Dhanushuya; S., Saravanan (International Journal of Contemporary Pediatrics, 2023)
Background: The survival of asphyxiated neonates has significantly increased in recent years because of numerous advancements in contemporary neonatal intensive care. The most popular and easily repeatable imaging method for the neonatal brain, the neurosonogram can demonstrate the most common types of cerebral injury in preterms and term infants. This study aims to analyse the value of cranial ultrasonography as an investigative tool for birth asphyxia babies (>34 weeks) will be evaluated to learn the morphology of various cerebral lesions and to compare clinical findings with neurosonogram results. Methods: An observational study was conducted in 75 neonates (>34 weeks) admitted in Government Cuddalore medical college with birth asphyxia. A detailed history and clinical examination was carried out according to the designed proforma. All the babies in the study group were subjected to cranial ultrasound and the morphology of findings studied. CUS findings were correlated clinically. Results: Among babies with HIE stage I, 89.7% had normal Cranial Ultrasound Findings, and 10.3% had abnormal findings. 43.3% babies had abnormal Cranial ultrasound findings in HIE stage II, and 70% had abnormal findings in HIE stage 3. Conclusions: Cerebral oedema was the commonest neurosonogram finding in Asphyxiated babies and HIE 3 had the maximum abnormal findings in our study. Since there is a positive correlation between the severity of hypoxic ischemic encephalopathy and cranial ultrasound findings, USG cranium can be performed as a screening tool in all neonates with birth asphyxia in whom additional investigations could not be performed.